2019
DOI: 10.1016/j.vetpar.2019.108921
|View full text |Cite
|
Sign up to set email alerts
|

Circulating immune complexes levels correlate with the progression of canine leishmaniosis in naturally infected dogs

Abstract: Dogs are the main domestic reservoir of Leishmania infantum, and in cases of uncontrolled infection, a strong humoral immune response is elicited, which is inefficient against the parasites. Previous studies have suggested that an adequate antigen/antibody ratio, with a moderate prevalence of antigens with respect to the antibodies, could result in the formation of circulating immune complexes (CIC) in canine leishmaniosis (CanL). Deposition of these complexes in tissues has been associated with vasculitis, uv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 62 publications
5
18
1
Order By: Relevance
“…In the present study, weight loss, lymphadenomegaly and exfoliative dermatitis were frequently observed in agreement with the findings of other studies and surveys [25,26,[44][45][46][47]. While renal disease, vasculitis, ocular and join disease have been observed less frequently, these are indicators of a worse prognosis because they are clinical signs related to immunocomplex deposition [48][49][50][51][52]. Additionally, other clinical signs have been sporadically observed such as neurological signs [53][54][55][56][57] or digestive disorders [58][59][60].…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, weight loss, lymphadenomegaly and exfoliative dermatitis were frequently observed in agreement with the findings of other studies and surveys [25,26,[44][45][46][47]. While renal disease, vasculitis, ocular and join disease have been observed less frequently, these are indicators of a worse prognosis because they are clinical signs related to immunocomplex deposition [48][49][50][51][52]. Additionally, other clinical signs have been sporadically observed such as neurological signs [53][54][55][56][57] or digestive disorders [58][59][60].…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, weight loss, lymphadenomegaly and exfoliative dermatitis were frequently observed in agreement with the findings of other studies and surveys [25,26,40,41,42,43]. While renal disease, vasculitis, ocular and join disease have been less frequently observed, these are indicators of a worse prognosis because they are clinical signs related to immunocomplex deposition [44,45,46,47,48]. Besides, other clinical signs have been sporadically observed such as neurological signs [49,50,51,52,53] or digestive disorders [54,55,56].…”
Section: Discussionsupporting
confidence: 92%
“…Immune-mediated mechanisms play a pivotal role in the pathogenesis of many clinical manifestations of CanL, particularly in the development of four principal types of glomerulonephritis, characterized by different grade of proteinuria and responsible for the development of renal failure, the most severe complication of CanL. Previous studies found a significant correlation between the level of antibody titers when assessed by IFAT and the severity of the disease (18)(19)(20), while a recent paper (21) demonstrated that CICs concentration is clearly related to the progression of CanL in naturally-infected dogs. In this study, remarkable was the demonstration of larger-size CICs (ranging from 100 to 400 nm) formed during the worsening of the disease, which was also characterized by an increase of IFAT titers.…”
Section: Discussionmentioning
confidence: 97%
“…This is quite different if compared with the probable acute stimulation due to the single intravenous injection of millions of parasites typical of an experimental infection. For this reason we believe important not only to assess the level of CICs during different stages of disease (21), but also to correlate the observed CICs levels with the time spent from the first demonstration of infection. The present study demonstrated also the usefulness of the ELISA kit for CICs detection.…”
Section: Groupmentioning
confidence: 99%
See 1 more Smart Citation